Acarbose plus metformin fixed-dose combination in the management of type 2 diabetes. (August 2014) - Joshi, Shashank R; Ramachandran, Ambady; Chadha, Manoj; Chatterjee, Sudip; Rathod, Rahul; Kalra, Sanjay
<x xml:space="preserve">Abstract</x> Introduction: The prevalence of type 2 diabetes mellitus (T2DM) is increasing worldwide. Concerns in the management of diabetes include drug-induced hypoglycemia, poor control of postprandial blood glucose level and weight gain. A carbohydrate-rich diet can cause more load on the intestinal cells producing α-glucosidase. Many patients need combination treatment based on their level of glycemic control and other associated parameters. In such cases, a therapy that provides effective glycemic control with minimal or no risk of adverse events like hypoglycemia or weight gain is highly desired. The chances of cardiovascular events are high in diabetes patients; hence, medicines providing benefits beyond glycemic control such as reduced cardiovascular risk factors may be ideal in such patients. Areas covered: Current available data are related to the rationale and clinical trials on the fixed-dose combination of <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=acarbose plus metformin&logicalOpe1=OR&field2=articletitle&text2=acarbose plus metformin&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">acarbose plus metformin in management of type 2 diabetes. Expert opinion: Combination therapy is routinely prescribed in the management of T2DM. Drugs with complimentary mechanisms should be used to maximize the efficacy of combination therapy. The combination of metformin and acarbose is a rational therapy because of their different and complimentary mechanisms of action, which provides effective glycemic control with additional cardiovascular benefits and minimizes adverse events.